2016
DOI: 10.5414/cp202623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel autoinjector for subcutaneous self-administration of belimumab in systemic lupus erythematosus

Abstract: Objective: To study self-administration and pharmacokinetics (PK) of subcutaneous (SC) belimumab in patients with systemic lupus erythematosus (SLE). Methods: Patients previously treated with belimumab self-administered belimumab 200 mg SC weekly for 8 weeks using an autoinjector. The primary endpoint was the proportion of patients able to self-administer their first and second dose (weeks 1 and 2) in the clinic. The proportion able to self-administer at weeks 4 and 8 (clinic) and weeks 3, 5, 6, and 7 (home) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, also in line with the PFS study, the incidence of pain associated with injection was reported as being of low intensity and decreased within 1 h of the injection and with each subsequent injection. This trend for a decrease in pain scores with increasing experience with injections has been previously reported with AI use in patients with systemic lupus erythematosus (15). This effect may be due to the patients change in expectations of pain, and/or the patient becoming more tolerant to pain with repeated self-injections.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, also in line with the PFS study, the incidence of pain associated with injection was reported as being of low intensity and decreased within 1 h of the injection and with each subsequent injection. This trend for a decrease in pain scores with increasing experience with injections has been previously reported with AI use in patients with systemic lupus erythematosus (15). This effect may be due to the patients change in expectations of pain, and/or the patient becoming more tolerant to pain with repeated self-injections.…”
Section: Discussionsupporting
confidence: 76%
“…Together, these findings suggest selfadministration is a viable treatment option that could be offered as an alternative to in-clinic administration for those patients who may prefer and can administer medication in the convenience of their home. Satisfaction with self-administration at home has been demonstrated in other therapeutic areas including rheumatoid arthritis, systemic lupus erythematosus, primary immunodeficiency disease, oncology, and multiple sclerosis (13)(14)(15)(16)(17)(18). Given the reduced need to attend the clinic, self-administration of mepolizumab in a home setting may also reduce the overall use of healthcare resources and improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the convenience and flexibility of treatment administration are important factors in patient treatment satisfaction. Initial trials of self-administered belimumab in healthy volunteers using an autoinjector device or prefilled syringe 14 and in patients with SLE using an autoinjector 15 have reported high levels of satisfaction with the belimumab autoinjector and a preference for subcutaneous administration to IV administration. 16 Subcutaneous administration of belimumab in patients with SLE has been further studied in a Phase III, randomized, double-blind, placebo-controlled trial to evaluate efficacy and tolerability after self-administration using the prefilled syringe during 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous administration of drugs is driving changes in global health-care systems [1,2]. In particular, novel device designs enable patient-centered concepts to healthcare and allow users across chronic disease states to routinely self-inject drugs at home, thereby eliminating the need of going to a hospital or infusion center [3][4][5][6][7]. Still, the delivery of around 1 mL of drug has been treated as upper limit using handheld autoinjectors, as the list of recently approved drug products indicates (see Table 1).…”
Section: Introductionmentioning
confidence: 99%